PEMANFAATAN MESIN PENCACAH DAN MESIN PRESS SEBAGAI ALAT PENGOLAH SAMPAH MENJADI PRODUK BERNILAI EKONOMIS - Dwi Rizka Zulkia (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2023)
The main contributor to the problem of slum settlements in urban areas is the issue of waste. Waste management that does not comply with the technical requirements encourages local governments to build TPS3R in residential areas. TPS3R KSM Kawa Begawe in Selindung Village is one of the real works of collaboration between the local government and the central government. TPS3R was founded in 2016 and developed in 2022 by providing organic and inorganic chopping machines, hydraulic press machines and maggot feed pulping machines. The purpose of this research is to find out whether this machine has been used optimally and has been able to improve the community's economy. The method used is a mixed method, where quantitative data is analyzed using simple calculations and qualitative data is analyzed using descriptive analysis. The results of the analysis found that as the population increases, TPS3R is urgently needed as an effort to reduce waste production by reducing disposable items or processing waste into other useful products and can open up new job vacancies so that it eventually becomes a source of income for the local community. In terms of the economic development plan, when this machine has been used optimally, this place will become a qualified source of income for the local community. The results of this study are certainly proof that TPS3R does not only answer the problem of environmental pollution caused by waste, but can also produce products that have economic value from waste processed at TPS3R KSM Kawa Begawe.